La réélection de Lula, changement de base - Hervé Théry; André Nagy (EchoGéo)
The re-election of Luiz Inácio da Silva, on October 29, 2006, in spite of the politico-financial scandals which marked the three last years of its first mandate is due mainly to a social and geographical change of its principal electoral base: supported until there by the industrial areas of the South, it was this time carried by North and Nordeste, the poor areas of the country, as shown by a series of maps based on the analysis of the electoral results.